SWOT ANALYSIS ON IKM KUE BAWANG BINA KARYA OF INDRAGIRI HULU REGENCY - Putri, Meilya Karya; Corrina, Fatti (LPPM Press STIE Indragiri Rengat, 2020)
his research aimed to analyze the external and internal environment in IKM Kue Bawang Bina Karya of Indragiri Hulu Regency by using SWOT Analysis. This research was conducted in December 2019. This research used mixed method, a combination between descriptive-qualitative and quantitative methods. The data used were primary and secondary data which were collected through interviews, observation, documentation and questionnaires. The subject and data sources of this research were the Consumers of IKM Kue Bawang Bina Karya of Indragiri Hulu Regency, the Owner of IKM Kue Bawang Bina Karya of Indragiri Hulu Regency, and The Industry and Trade Agency of Indragiri Hulu Regency. The results of this research showed that, currently, IKM Kue Bawang Bina Karya supported aggressive strategies that are applicable, namely Market Development Strategy, Market Penetration Strategy, Product Development Strategy, Forward Integration Strategy, Backward Integration Strategy, Horizontal Integration Strategy, and Diversification Strategy.